2004
DOI: 10.1021/jf049169c
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Contents of Carotenoids and Vitamin E during Tomato Processing

Abstract: The aim of this study was to investigate the effect of different types of tomato processing on contents of lycopene, beta-carotene, and alpha-tocopherol. Samples of tomato sauce, tomato soup, baked tomato slices, and tomato juice were taken at different times of heating, respectively, after each step of production. HPLC was used to analyze contents of carotenoids and vitamin E. Due to the loss of water during thermal processing, contents of lycopene, beta-carotene, and alpha-tocopherol on a wet weight basis in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
110
3
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 180 publications
(134 citation statements)
references
References 33 publications
19
110
3
2
Order By: Relevance
“…31 Also, the contents of chlorophyll a and b significantly increased during concentration process. Seybold et al 33 found that, due to the loss of water during thermal processing of tomato, contents of lycopene and carotenoids on a wet weight basis increased. On a dry weight basis, contents of lycopene increased or decreased depending on the origin of the tomato fruits used, whereas the β-carotene contents decreased or were quite stable.…”
Section: 31mentioning
confidence: 99%
“…31 Also, the contents of chlorophyll a and b significantly increased during concentration process. Seybold et al 33 found that, due to the loss of water during thermal processing of tomato, contents of lycopene and carotenoids on a wet weight basis increased. On a dry weight basis, contents of lycopene increased or decreased depending on the origin of the tomato fruits used, whereas the β-carotene contents decreased or were quite stable.…”
Section: 31mentioning
confidence: 99%
“…The contents of lycopene significantly increased from 0.08 µmol/L to 0.80 µmol/L (Vuong et al, 2002). Thus, lycopene is available from these fruits.…”
Section: Discussionmentioning
confidence: 86%
“…Rosehip purées were analysed on their carotenoid contents as recently described for tomato products elsewhere (Seybold et al, 2004).…”
Section: Analysis Of Carotenoidsmentioning
confidence: 99%
“…In plants, they help in photosynthesis and prevent the oxidation of chlorophylls; in human beings, consumption of β-carotene and lutein, the two most important dietary carotenoids, reduces the risk of lung cancer and chronic eye diseases like cataracts [38]. Slight decreases in total carotenoids content were observed during hot-air drying of carrots [39]; moreover, coupled blanching and drying releases carotenoids from lipid membranes and complexes, resulting in better bio-availability [40,41]. Despite this positive effect, heat induces the isomerization of carotenoids from trans to cis, which is more susceptible to oxidation [42].…”
Section: Carotenoidsmentioning
confidence: 99%